Bluecap: A geospatial model to assess regional economic-viability for mineral resource development. (June 2020) - Walsh, Stuart D.C.; Northey, Stephen A.; Huston, David; Yellishetty, Mohan; Czarnota, Karol
Abstract: Frontier mineral exploration is often exclusively focused on assessing geological potential without consideration for the economic viability of resource development. This strategy may overlook potentially prosperous zones for more geologically-favoured but financially-disadvantageous regions, or conversely, may introduce implicit biases against potential developments without due regard to underlying economies of scale or proximity to infrastructure. Accordingly, in this paper, we introduce a numerical model aimed at identifying economic fairways, i.e. areas permissive to mineral development from an economic perspective. The model, Bluecap, combines large-scale infrastructure and geological datasets to conduct geospatial analysis of the economic-viability of mining operations across Australia. We provide a detailed description of the inputs and assumptions that underlie the cost models employed in Bluecap, outlining the methods used to evaluate mining, processing, administrative and infrastructure expenses. We also describe the databases used by the model to evaluate available infrastructure, transportation distances and depth of cover. Finally, we present examples that demonstrate the use of the Bluecap model on regions around Mount Isa and the Murray Basin to verify its ability to evaluate commercially feasible mineral prospects. While the immediate utility of this model stands to benefit mineral explorers, its ability to map mineral economic fairways also provides an objective, evidence base to underpin government decision making with respect to position of new infrastructure and consideration of competing land use claims.